Impulsivity Moderates Skin Conductance Activity During Decision Making in a Modified Version of the Balloon Analog Risk Task - Hüpen, Philippa; Habel, Ute; Schneider, Frank; Kable, Joseph W.; Wagels, Lisa (Frontiers in Neuroscience, 2019)
Individual differences in traits such as impulsivity and emotional processing of risk and reward have been linked to decision making and may underlie divergent decision making strategies. It is, however, unclear whether and how far individual differences in these characteristics impulsivity and emotional processing jointly influence decision making. Here, we aimed to investigate the roles of skin conductance responses, a psychophysiological marker of emotional processing of risk processing and impulsivity, as assessed by the Barratt Impulsiveness Scale 11 on decision making. Forty- six healthy participants performed a modified version of the Balloon Analogue Risk Task (BART), where reward and explosion risk are manipulated separately. Participants are informed about whether they play a high versus low reward and high versus low explosion risk condition. The exact risk and reward contingencies are, however, unknown to participants. Participants were less risk-taking under high, compared to low explosion risk and under high reward, compared to low reward on the modified BART, which served as a validation of the paradigm. Risk-taking was negatively related to skin conductance responses under high explosion risk. This relationship was primarily driven by individuals with relatively high levels of impulsivity. However, impulsivity alone was not found to be related to decision making on the modified BART. These results extend evidence that skin conductance responses may guide decision making in situations, where participants are informed about explosion risk level (high versus low), which might be differentially moderated by different levels of impulsivity.